2004
DOI: 10.1007/s00586-003-0665-1
|View full text |Cite
|
Sign up to set email alerts
|

Condition-specific outcome measures for low back pain

Abstract: A literature review of the nine most widely used, condition-specific, self-administered assessment questionnaires for low back pain has been undertaken. General and historic aspects, reliability, responsiveness and minimum clinically important difference, external validity, floor and ceiling effects and available languages were analysed for the nine most-used outcome tools. When considering which condition-specific measure to employ, the present overview on assessment tools should provide the necessary informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 60 publications
5
62
0
Order By: Relevance
“…Effective scientific evaluation governed by reliable scientific principles is essential. 18,19 Thus, we fully agree with those [20][21][22][23][24][25][26][27] who recommend the use of multiple means of measurement that respect cultural, social, and personal differences present in the patients that we propose to evaluate, and it is in this manner that we developed this prospective study.…”
Section: Discussionsupporting
confidence: 77%
“…Effective scientific evaluation governed by reliable scientific principles is essential. 18,19 Thus, we fully agree with those [20][21][22][23][24][25][26][27] who recommend the use of multiple means of measurement that respect cultural, social, and personal differences present in the patients that we propose to evaluate, and it is in this manner that we developed this prospective study.…”
Section: Discussionsupporting
confidence: 77%
“…The ICC reported in the present study for the German ODI was higher than those reported in previous studies, even though many of the latter used shorter test-retest intervals (median 4 days, ICC=0.91 [29]; 1 week, 0.83 [22], 0.94 [15]; 2 days, 0.88 [23], 2 weeks, 0.94 [26]; 4 weeks, 0.90 [21], 6 weeks, 0.84 [11]). The weighted j values for the individual questions were moderate to very good, ranging from 0.59 (for the ''lifting'' question) to 0.85 (for ''walking''); no j values for the ODI have previously been reported in the literature for comparison [32]. Although the j values reported in the present study indicate that some of the individual questions could be used reliably in sub-analyses, as done in previous studies [12], the questionnaire was originally intended only to provide a sum-score for disability.…”
Section: Construct Validity Of the Odimentioning
confidence: 77%
“…Subjects completed the ODI (version 2.1a) and the QDS as condition-specific PROMs, the general construct of which have been published previously several times [11,40]. The total score of both PROMs were converted to rate of disability in percentage using the proportional recalculation method.…”
Section: Measurement Toolsmentioning
confidence: 99%
“…Several different PROMs, measuring spine-related disability, have been developed and published [3,11]. The Oswestry Disability Index (ODI) [12,13] and the Quebec Back Pain Disability Scale (QDS) [14,15] are two reliable, valid and widely used PROMs in spine care that have been validated for use with numerous languages since first being reported in English.…”
Section: Introductionmentioning
confidence: 99%